2017
DOI: 10.1177/0272989x17734538
|View full text |Cite
|
Sign up to set email alerts
|

Online, Interactive Option Grid Patient Decision Aids and their Effect on User Preferences

Abstract: The use of decision aids for some, but not all health decisions, was accompanied by a shift in user preferences. Users typically valued information associated with risks, and chose more risk averse options after completing the interactive tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Our previous work indicated that FAQs 1, 3, and 8 shifted user preferences to not having the PSA screening test. In this study, FAQs 1, 3, and 7 shifted preference in the same direction, confirming that risk information (FAQs 7 and 8 both discuss risk) may be the active ingredient in the PSA Option Grid responsible for the shift [9]. FAQs 7 and 8 discuss the risk of the PSA test and the risk of the prostate biopsy, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our previous work indicated that FAQs 1, 3, and 8 shifted user preferences to not having the PSA screening test. In this study, FAQs 1, 3, and 7 shifted preference in the same direction, confirming that risk information (FAQs 7 and 8 both discuss risk) may be the active ingredient in the PSA Option Grid responsible for the shift [9]. FAQs 7 and 8 discuss the risk of the PSA test and the risk of the prostate biopsy, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…The FAQs represented nominal independent variables and were inserted as factors in the model. Due to the fact that multiple treatment options are being compared for each FAQ, we decided that FAQs with a P value of ≤.02 would be considered statistically significant in terms of shifting user preference [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole of the ‘Dialysis Choice’ PDA contributed to the decision-making process, but the patients identified the overview of options and the value clarification tool as being particularly helpful. An Option Grid is a specific type of overview of options, and research has shown that, for some health decisions, an Option Grid supports patients in the decision-making process 45. From a healthcare perspective, the Option Grid has been found to be easy to use to facilitate patient involvement in the decision-making process 46.…”
Section: Discussionmentioning
confidence: 99%
“…This decision aid shifts user preferences regarding treatment, but improvements in satisfaction or adherence have not been documented. 27 Both of these decision aids focus on whether to take statins and do not provide information on the comparative effects of statins and patients’ preferences regarding these benefits and harms. The interactive tool evaluated in this study is therefore novel in combining the results of published network meta-analyses with user preferences.…”
Section: Discussionmentioning
confidence: 99%